Implementasi Sistem Pelayanan Publik di Kantor Desa Kumantan - Nasari, Fina; Oktorina, Fenty Kurnia; Ridwan, Muhammad; Putri, Tara Liana Ramadhani; Fitri; Nofiar. AM, Andri; Antoni Pribadi (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
Kumantan Village is a village administratively located in Bangkinang District, Kampar Regency. Kumantan Village has an area of 16 km² with a population of 6,146 people. The dissemination of information in Kumantan Village has not been digitalized, where information is distributed through RW and RT assistance or directly to residents. Public service activities in Kumantan Village are still conducted manually. This situation results in suboptimal public services and information dissemination. The proposed solution to address this issue is the development of a public service information system to streamline correspondence management and broaden information dissemination. The community service program for implementing the public service information system has been conducted and is expected to resolve the identified problems.